Kom al-Ahmer - Kom Wasit I excavations in the metelite nome, Egypt : ca. 700 BC - AD 1000 - Kenawi, Mohamed; Mondin, Cristina (Archaeopress archaeology., 2019)
This volume presents the results of the Italian archaeological mission at Kom al-Ahmer and Kom Wasit, Beheira, Egypt between 2012 and 2016. It provides details of the survey and excavation results of the different occupation phases, which range from the Late Dynastic to the Early Islamic period.